Біолого-морфологічні особливості рослин роду Lophanthus Adanson при інтродукції в Кременецькому ботанічному саду - Melnychuk, O.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to conduct a comprehensive study of the biological and morphological characteristics of plants of the genus Lophanthus Adanson depending on the feeding area under the conditions of the Kremenets Botanical Garden. Material and methods. The research was carried out in the Kremenets Botanical Garden during 2016–2018. Studied the laws of the passage of growth processes and the development of plants of Lophanthus, depending on the plant nutrition area, it has been determined the soil similarity without preliminary preparation depending on the time of sowing. The material for research was plant specimens L. anisatus cv. Siniy veleten and cv. Leleka. Seeds of plants were obtained from the M.M. Gryshko National Botanical Garden of the NAS of Ukraine. The trial included four variants in three repetitions. Variants differed according to the arrangement of plants: 20 × 20, 35 × 35, 45 × 45, 70 × 70 cm. Such methods as field, laboratory and measurement-weighted have been used. Results. The plants reproduce well by the seminal method, forming self-seedling. Not damaged by diseases and pests, drought and winter hardiness. The genotypes studied are commonly adapted to local conditions. Conclusions. It has been established that the determining factor of the active growth of plants Lophanthus, the optimum area of nutrition, namely – 4900 cm2, which makes it possible to form a large overland mass and powerful root system. It was established that the soil similarity of the seed without preliminary preparation has a direct dependence on the sowing dates. The best seeds sprouts of L. anisatus were observed during sowing the I decade March (82 %), II decade April (80 %), and the highest were the average indices of similarity of seed sown in the III decade April (95 %).